Analysis of Financial Performance based on Liquidity and Profitability Ratio (Case Study on PT Unilever in period 2013-2017) - Ali, Muhammad; Andari, Diah; Indah Bayunitri, Bunga; Ariffian, Andry; ., Sugiartiningsih (International Journal of Engineering and Technology, 2018)
This research method uses secondary data from PT Unilever's financial statements in the period 2013 to 2017, the final results of which can be used for decision making for management or outside parties that have a need for the company. The purpose of this analysis is carried out namely as a basis for making relevant decisions so that the company or interested parties have a minimum basis for decision making. The results of this analysis indicate that the company is declared to be less liquid when viewed from the results of liquidity ratio analysis based on theory, but stated either when viewed or compared with other leading companies. The results of the profitability ratio analysis are above the industry average and in practice the company is indeed in a stable condition. To compare with theory and results of conclusions based on practice, so that it can be assessed that companies use funds effectively and can be judged that the company is in good condition.Â